An Egyptian Mummified Crocodile from the Kyiv-Pechersk Lavra National Preserve (Ukraine): Archaeological and Morphological Considerations - Yanish, Yevheniia; Piombino-Mascali, Dario; Rosendahl, Wilfried; Chen, Shidong; Oras, Ester; Tarasenko, Mykola (Archaeologia Lituana, 2025)
This study presents the first examination of an Egyptian mummified crocodile from the collection of the Kyiv-Pechersk Lavra National Preserve (Ukraine). Archival research established that the specimen was donated to the Archaeological Museum at St. Volodymyr’s University in 1860 by Dr. Joseph Shkuratovsky who likely obtained it in Upper Egypt in the mid-19th century. The mummy had never been studied by Egyptologists, bio-archaeologists, or zoologists. Radiocarbon dating and chemical analysis of embalming substances were conducted using standard protocols. The radiocarbon results suggest a Ptolemaic Period origin (332–30 BC), although possible reservoir effects may have influenced the date. Beyond presenting this unique find to a wider audience, a key objective was to explore possible morphological criteria for distinguishing the Nile crocodile (Crocodylus niloticus) from the West African crocodile (Crocodylus suchus), both sympatric species present in ancient Egypt. Drawing on Etienne Geoffroy Saint-Hilaire’s early observations and subsequent morphometric data, the structure of the external mandibular fenestra in this specimen was examined and compared to other examples, both modern and archaeological. The fenestra of the examined specimen exhibits features more typical of C. suchus. However, it is of importance to note that crocodile mummies cannot be assumed to represent C. suchus without a robust series of genetically confirmed specimens. Thus, the present observations are preliminary and should be regarded as a working hypothesis to be tested against other larger, well-documented datasets and utilizing DNA analyses. Morphological examination also revealed evidence that the crocodile was intentionally killed – likely by a single, precise stab wound to the neck – and that the injury was carefully concealed, suggesting a broader and more deliberate practice of sacrificial killing than previously recognized. This study contributes new archaeological, historical, and morphological data to the growing body of research on animal mummification in ancient Egypt, while underscoring the need for further work on species identification criteria.
Keywords: crocodile mummy; Egypt; Ptolemaic Period; species identification; morphometry; embalming practices